2018
DOI: 10.1021/acs.jpcc.8b03023
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom-Induced Molecular Asymmetry Tunes Quantum Interference in Charge Transport through Single-Molecule Junctions

Abstract: We studied the interplay between quantum interference (QI) and molecular asymmetry in charge transport through a single molecule. Eight compounds with five-membered core rings were synthesized and their single-molecule conductances were characterized using the mechanically controllable break junction (MCBJ) technique. It is found that the symmetric molecules are more conductive than their asymmetric isomers and there is no statistically-significant dependence on the aromaticity of the core. In contrast, we fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 29 publications
4
60
0
2
Order By: Relevance
“…30 In contrast, a study on a comparable series of 2,5-disubstitutedfuran, -pyrrole, -thiophene and -cyclopentadiene derivatives with pyridyl anchors found no statistically significant dependence of the conductance on the aromaticity of the core. 31 For molecules with tricyclic cores, it has been shown that increasing aromaticity at the core decreases the conductance for the para-linked molecules (dibenzothiophene < carbazole < dibenzofuran < fluorene) with pyridyl anchors, 32 in agreement with Venkatarman et al 30 However, the sequence is different for the isomers where the tricyclic core is meta-linked into the backbone (dibenzothiophene ≈ dibenzofuran < carbazole ≈ fluorene). 32 It is therefore of particular interest to explore the effect of incorporating 4n π-electron antiaromatic rings into the backbone of molecules that are wired into junctions.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…30 In contrast, a study on a comparable series of 2,5-disubstitutedfuran, -pyrrole, -thiophene and -cyclopentadiene derivatives with pyridyl anchors found no statistically significant dependence of the conductance on the aromaticity of the core. 31 For molecules with tricyclic cores, it has been shown that increasing aromaticity at the core decreases the conductance for the para-linked molecules (dibenzothiophene < carbazole < dibenzofuran < fluorene) with pyridyl anchors, 32 in agreement with Venkatarman et al 30 However, the sequence is different for the isomers where the tricyclic core is meta-linked into the backbone (dibenzothiophene ≈ dibenzofuran < carbazole ≈ fluorene). 32 It is therefore of particular interest to explore the effect of incorporating 4n π-electron antiaromatic rings into the backbone of molecules that are wired into junctions.…”
Section: Introductionsupporting
confidence: 60%
“…Biphenyl derivative 6 shows slightly lower conductance than that of 8, because of the larger torsion angle between the two phenyl rings of 6, compared to the planar fluorene unit of 8. 31,[53][54][55] Furthermore, the conductance of antiaromatic molecule 4 is comparable with that of 6 and 8, and no enhancement in charge transport due to the biphenylene unit in 4 is observed. This agrees with a previous comparison of conductance through a biphenylene and a fluorene core reported by Venkataraman et al 40 To reveal the evolution of the stretching process, 2D conductance-distance clouds were constructed by normalizing more than 1000 typical conductance traces to a relative zero point at 10 −0.3 G 0 and plotted as intensity graphs 54 as shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…5,20,28 However, the presence of pendant groups bearing different substituents changes the electronics of the molecule and can affect the position and the shape of the QI feature with respect to the Fermi energy ( E f ) inside the junction, thereby affecting the measured conductance differently. This phenomenon has been explored theoretically and experimentally in the case of meta-substituted benzene and biphenyl in single-molecule junctions, but not in large-area junctions 14,18,19,29. Moreover, the torsional angle introduced in the core by the bulky pendant groups might also affect the QI features by means of through-space interactions, which are expected to differ in single-molecule junctions and in monolayers, in which molecules tend to planarize 16…”
Section: Design and Transport Calculationsmentioning
confidence: 99%
“…18a in which different 5-membered (hetero)cycles were used as the central ring. 76 For the symmetrically substituted series (s5-X), where in all cases the lone pair of a D in one anchoring position can be delocalised to an A at the other (Fig. 18b), CQI is expected according to ECAR-1.…”
Section: Limitations Of Ecarsmentioning
confidence: 98%